2001
DOI: 10.1243/0954405011515433
|View full text |Cite
|
Sign up to set email alerts
|

Turning particulate metal matrix composites: Experimental study of the evolution of the cutting forces, tool wear and workpiece surface roughness with the cutting time

Abstract: This paper presents an experimental study of the evolution of the cutting forces, tool wear and surface roughness during the turning of the particulate metal matrix composite A356/20/SiCp-T6. The experimental work was developed through the continuous measurement of the cutting forces with an appropriate piezoelectric dynamometer. The wear type was identified and its evolution with cutting time was measured. Inserts with polycrystalline diamond (PCD) were tested. The surface roughness was evaluated with a profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Higher cutting speeds are not advantageous in all the cases except when PCD and CBN tools are used 9,10 . Davim 11 identified that the medium cutting speed ranges from 200-450 m/min are recommended for carbide and coated carbide tools for better surface finish and reduced tool wear. The maximum cutting speeds used with PCD tools is up to 700 m/min.…”
Section: Introductionmentioning
confidence: 99%
“…Higher cutting speeds are not advantageous in all the cases except when PCD and CBN tools are used 9,10 . Davim 11 identified that the medium cutting speed ranges from 200-450 m/min are recommended for carbide and coated carbide tools for better surface finish and reduced tool wear. The maximum cutting speeds used with PCD tools is up to 700 m/min.…”
Section: Introductionmentioning
confidence: 99%
“…A similar experiment has been conducted on turning of MMCs using PCD inserts and found that the cutting forces increases with flank wear of the inserts. The feed and depth forces are more sensitive to this increase [9]. A predictive model has been developed while machining of Al-SiC-MMC using ANOVA and ANN.…”
Section: Introductionmentioning
confidence: 99%
“…As result of these properties and potential applications, a great necessity exits to understand the questions associated with the production and machining of such materials. Machining MMCs is a rather complex task owing to its heterogeneity and to the fact that reinforcements are extremely abrasive [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The machinability of MMCs reinforced with particles of SiC (20%) using PCD tools was studied having in consideration the evolution of the cutting time of the tool wear, the cutting forces and the surface roughness workpieces [1][2][3]. Later, was evaluated the performance of the CVD diamond tools in machining of these composites [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation